Che cos’è un disegno e perché si disegna - Giuseppe Di Napoli (Rivista di Estetica, 2011)
A simple line drawing can reproduce a vast collection of phenomenal discontinuities: optical, material, chromatic, and also of density, dimension, resistance. All these discontinuities correspond to physical realities quite different from each other. This fact leads us to consider that our brain can retrieve from a pencil stroke a broad and amazing lot information at several levels, from the physical to the phenomenological, from the logical to the cognitive. Drawing demonstrates the existence in our brain of a complex communication web between the visual and action cortical areas and the zones of the paleo encephalon, indicating the biological necessity of establishing a continuity between vision and action, between representation and abstraction. Thus, drawing is a natural language, and represents a biological and expressive invariant; it is also a cultural language, the result of technical and symbolic development of a civilization; and it is, finally, an universal language, indeed the main communication system between different cultures.